What knowledge (s)? Reflections on knowledge policies, the academic field and the Ecuadorian indigenous movement - Walsh, Catherine (2016)
This article analyzes the manner in which the cultural and identity politics of the Ecuadorian indigenous movement have contributed to the development, recuperation and (re)creation of new forms of knowledge and social agency. By emphasizing the construction of epistemological frameworks, both indigenous and intercultural, that challenge the dominant geopolitics of knowledge and the disciplining of subjectivity, the article demonstrates what is actually at stake with the question: What knowledge(s)?